Relationship between the left atrial and pulmonary vein effective refractory period and the development of early atrial fibrillation recurrence after radiofrequency pulmonary vein isolation. First results - A. T. Kozhenov; S. N. Azizov; O. V. Khlynova (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To assess the relationship between the left atrial (LA) and pulmonary vein (PV) effective refractory period and the development of early atrial fibrillation (AF) recurrence after radiofrequency pulmonary vein isolation (PVI).Material and methods. The study included 35 patients with persistent AF refractory to antiarrhythmic therapy (AAT). In all patients, LA and PV effective refractory period (ERP) was assessed, followed by radiofrequency antral PVI. Depending on the ERP values, the patients were divided into 2 groups. Group 1 (n=15) included patients with mean LA and PV ERP values ≥240 ms, while group 2 (n=20) consisted of patients with mean LA and PV ERP values <240 ms. The evaluation of early AF recurrence, depending on the obtained ERP values, was carried out in the first 3 months.Results. We obtained following ERP values: group 1 — LA (LA ap pendage) 252±8,9 ms; left superior PV (LSPV) — 252±12,1 ms; left inferior PV (LIPV) — 257,3±8,15 ms; right superior PV (RSPV) — 254,6±11,3 ms; right inferior PV (RIPV) — 260±9,05 ms; group 2 — LA 230±12,1 ms; LSPV — 205±10,5 ms; LIPV — 186,6±22,05 ms; RSPV — 212,2±14 ms; RIPV — 218,8±11,1 ms. During the 3-month follow-up of group 1 patients, there were no recurrences after PVI. Group 2 had 7 early AF recurrences. Correlation analysis revealed a significant inversely proportional relationship (-0,349; p=0,03) between ERP values and the recurrence rate in the groups.Conclusion. The first results demonstrate an inversely proportional relationship between the mean PV and LA ERP and the development of early AF recurrence, which makes it possible to consider the PV and LA ERP <240 ms as a likely predictor of early AF recurrence. However, this fact requires the study continuation with an increase in the sample and an appropriate statistical analysis.